Surgical stabilization of rib fractures in symptomatic COVID-19: A case report. (October 2021) - Wu, Jin; Saraswat, Nirvana; Harris, Kevin; Goslin, Brent; DeVoe, William
Abstract: Severe chest wall injury following trauma is a significant contributing factor to respiratory failure and need for mechanical ventilation in multiply injured patients. Surgical stabilization of rib fractures (SSRF) is increasingly considered to be advantageous in this population. Surgical stabilization has been shown to improve multiple outcomes including ventilator avoidance, liberation from mechanical ventilation, and diminished pulmonary complications in the trauma population, particularly when performed early. During the coronavirus disease 2019 (COVID-19) pandemic, ventilators have become a scarce resource, and conservative strategies have become a critical component of intensive care. We present a report of the perioperative outcome of SSRF in a geriatric polytrauma patient who initially presented after a mechanical fall and co-existing symptomatic COVID-19.